Analysis of Coal Mining Legal Instruments and the Powerlessness of the State in Restricting Natural Destruction Activities by Corporations (Case Study of the Implementation of the Law on Coal Mining Against Ecological Environmental Damage in Indonesia) - Zulqarnain, Zulqarnain -; Riza, Fikri - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Management of Natural Resources (SDA) through mining has generated huge income for the Indonesian government. In addition, mining activities have caused damage to the natural environment that poses a threat to the future of human life. The government makes every effort to restrict mining activity so as not to harm the environment. A set of legal laws has been developed, but mining activities continue to harm the environment.Why is this so? What's the issue? Is the mining law still ineffective? Or weak execution of law? This research solves these questions at least. This study is qualitative in nature. This study's data were collected through a series of interviews, a review of the relevant literature, and a document analysis. The study's conclusions show that the laws controlling mining have limited the options available to mining entrepreneurs for carrying out their operations without endangering the environment. On the other hand, the finding of unreclaimed mining sites suggests that the legal process has not been followed correctly or diligently enough.